The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M (The American psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the "gender binary," played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals' identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).